Case of Georgia v. Russia (I) (Just Satisfaction). Issue 3 (July 2019) - Ioffe, Yulia
Abstract : In Georgia v. Russia (I) (Just Satisfaction), the Grand Chamber of the European Court of Human Rights (ECtHR or Court) ordered the Russian Federation to pay Georgia EUR 10 million as reparation for Russia's "coordinated policy of arresting, detaining and expelling Georgian nationals" in the autumn of 2006 (paras. 51, 80). In so doing, the Court reaffirmed its position from Cyprus v. Turkey (IV) (Just Satisfaction) that financial compensation for non-pecuniary damage can be awarded in interstate cases. Although Georgia v. Russia (I) (Just Satisfaction) marks the development of a new line of ECtHR jurisprudence, it is unlikely that the decision will effectively prevent further mass violations of the European Convention on Human Rights (ECHR or Convention) by the states parties or offer fair compensation to the victims of such violations.